Humanisme dalam Serat Jangka Jayabaya Perspektif Javanese Wordview - Sasmita, Gusti Garnis; Joebagio, Hermanu; Sariyatun, Sariyatun (Program Studi Studi Agama-Agama, Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri (UIN) Sunan Ampel Surabaya, 2018)
Serat Jangka Jayabaya is a literary work that can be used as a source of historical learning. The local genius of Javanese worldview is reflected in humanism values in the manuscript. Which is much misunderstood by most people even historians. This study uses qualitative research methods that reveal the value of Jayabaya humanism based on content, authorship and axiological manuscripts through interviews and literature studies. The results show that the concept of